Sosialisasi Pentingnya Endurance Dalam Meningkatkan Kinerja Pelatih Olahraga di Kecamatan Sidareja Tahun 2021 - Rama Cipta Prasetia; Dian Imam Saefulah; Fahmi Wiram (Pusat Riset dan Inovasi Nasional, 2021)
Socialization of the importance of resilience in improving the performance of sports trainers in the Sidareja sub-district aims to ensure that the performance of trainers can carry out activities for longer periods continuously. Explaining and training about the meaning of endurance provides information about the importance of maintaining endurance to improve trainer performance. Trainers are given knowledge about endurance as well as evaluation methods using endurance measurement tests, which are carried out using the Blipt Test. This test involves running back and forth for 20 meters or starts with a gradual running from slow to fast, creating a challenge for the athlete to stay on track with increasing running times.